Inertial sensor-based measures of gait symmetry and repeatability in people with unilateral lower limb amputation. (February 2020) - Clemens, Sheila; Kim, Kyoung Jae; Gailey, Robert; Kirk-Sanchez, Neva; Kristal, Anat; Gaunaurd, Ignacio
Abstract: Background: People with lower limb amputation often walk with asymmetrical gait patterns potentially leading to long-term health problems, ultimately affecting their quality of life. The ability to discreetly detect and quantify the movement of bilateral thighs and shanks using wearable sensor technology can provide additional insight into how a person walks with a lower limb prosthesis. This study investigated segmental symmetry and segmental repeatability of people with unilateral lower limb amputation, examining performance of the prosthetic and intact limbs. Methods: Gyroscope signals were recorded from four inertial measurement units worn on bilateral lower limb segments of subjects with unilateral lower limb amputation during the 10-m walk test. Raw angular velocity signals were processed using dynamic time warping and application of algorithms resulting in symmetry measures comparing similarity of prosthetic to intact limb strides, and repeatability measures comparing movement of one limb to its consecutive strides. Findings: Biomechanical differences in performance of the prosthetic and intact limb segments were detected with the segmental symmetry and segmental repeatability measures in 128 subjects. More asymmetries and less consistent movements of the lower limbs were exhibited by subjects with transfemoral amputation versus transtibial amputation ( p  < .004, Cohen's d = 0.65–1.1). Interpretation: Sensor-based measures of segmental symmetry and segmental repeatability were found to be reliable in detecting discreet differences in movement of the prosthetic versus intact lower limbs in amputee subjects. These measures provide a convenient tool for enhanced prosthetic gait analysis with the potential to focus rehabilitative and prosthetic interventions. Highlights: Wearable sensors can be used to detect movements of the four lower limb segments Segmental movement analysis of prosthetic gait exposes differences in limb motion Segmental symmetry and repeatability of prosthetic gait varies by amputation level Segmental symmetry and repeatability of prosthetic gait varies between limbs Segmental symmetry and repeatability provide greater insight during gait analysis